Left atrial volume quantification using coronary calcium score scan: Feasibility, reliability and reproducibility analysis of a standardized approach. (June 2019) - Cardona, Andrea; Trovato, Vincenzo; Nagaraja, Haikady N.; Raman, Subha V.; Harfi, Thura T.
Abstract: Background: Left atrial volume (LAV) is an independent prognosticator of cardiovascular events. We investigated whether LAV could be accurately and reliably measured using coronary calcium score (CAC) scan. Methods: We retrospectively selected consecutive patients that underwent coronary CT angiography (CCTA) and CAC scans. A standardized approach to calculate LAV on images was implemented. The measurements of the LAV on CAC scans and CCTA were performed one to three weeks apart in a random fashion by two readers blinded to the results of each other. The LAV measurements from CAC scan were compared to those from CCTA using correlation analysis. Inter-observer and intra-observer agreement of LAV measurement using CAC scan was evaluated. Results: Final analysis included one hundred subjects, mean age 52 ± 12 years, 48% male. There was a trend of a marginally larger, albeit not clinically significant, mean LAV calculated using CAC scan compared to that using CCTA: 74.3 vs. 71.0 mL: p < 0.001; for reader 1, and 71.7 vs. 71.2 mL p = 0.06 for reader 2, respectively. LAV using CAC scan and CCTA were highly correlated ( R = 0.954, p < 0.001 for reader1 and R = 0.945, p < 0.001 for reader 2). There was high reproducibility within each reader with ICC of 0.951 and 0.989 for readers 1 and 2, respectively ( p < 0.001). Finally, there was high inter-observer agreement as indicated by R of 0.97 and ICC of 0.96 ( p < 0.001 for both). Conclusions: Quantification of LAV from CAC scan using the proposed standardized approach is feasible, highly reliable and reproducible as compared to CCTA. Highlights: Left atrial volume (LAV) measurement from coronary calcium (CAC) scan is feasible. The ECG gating of CAC scan improves delineation of the left atrium. LAV measurement from CAC scan is highly accurate and reproducible. Inclusion of LAV from CAC scan can potentially improve risk prediction.